Hyperuricemia: When to treat? - Maharjan, Rony (Journal of General Practice and Emergency Medicine of Nepal, 2019)
Hyperuricemia can lead to gouty arthritis and Nephrolithiasis; however asymptomatic hyperuricemia does not need urate lowering therapies. The treatment should be initiated only if there are two or more acute gout attacks per year, presence of tophi or renal stones or chronic kidney disease stage two or more.